Metode Penyampaian Pesan Dakwah Dalam Meningkatkan Pemahaman Agama Masyarakat Pada Pengajian Rutin Malam Sabtu Di Masjid Miftahul Jannah Perumahan Griya Sukarame Bandar Lampung - tansil, glenaldy; Khairullah, Khairullah; Umi Rojiati (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2026)
Regular Islamic study groups (Koran) are a means of da'wah (Islamic outreach) that play a strategic role in enhancing religious understanding in the community, particularly in urban environments with high levels of activity and limited social interaction. This study aims to analyze the methods of delivering Islamic outreach messages and their impact on improving the congregation's religious understanding during regular Saturday night Islamic study groups at the Miftahul Jannah Mosque in the Griya Sukarame Housing Complex, Bandar Lampung. This study uses a qualitative approach with field study methods through observation, interviews, and documentation. The research stages include data collection, data reduction, data presentation, and drawing conclusions. The results show that the da'wah delivery methods used include interactive lectures and dialogues or questions and answers tailored to the needs of the congregation. These methods have proven effective in improving religious understanding, as demonstrated by the congregation's increased ability to understand the material, active participation in Islamic study activities, and changes in worship behavior in daily life. In addition, Islamic study activities also contribute to strengthening social interactions based on Islamic values ​​within the community. Thus, regular community-based Islamic study groups can be an effective model of religious development in increasing religious awareness in urban communities